An exploration of the experiences of students in a guided pathways model program - Madison, Clarence Y., Sr. (Kansas State University, 2022)
The purpose of this case study was to examine student experiences within an established guided pathways model program that integrated a system of student support to increase on-time graduation rates. Four research questions guided the investigation: (1) How did the participants describe the college’s approach to helping students enter an academic pathway?; (2) How did the participants describe the college’s approach to clarifying the students’ pathways that helped them to choose the right career to keep them on track to ensure students’ are learning?; (3) How did the participants describe the guided pathways model experiences to keep students on track with their career goals?; and, (4) How did the participants describe the college’s approach to ensure that learning happened with intentional outcomes for students? Key findings from this study were as follows: 1) an effective guided pathways model aligns individualized plans using comprehensive academic roadmaps co-created by academic advisers and students; 2) students who met with an academic adviser early in the admission process were likely to complete their program on time; and, 3) regular visits with academic advisers helped to keep students focused on their program of study while navigating life’s challenges. Lastly, the community college participating in this study invested sufficient professional development funds to support guided pathways services. For example, the college supported professional development to ensure faculty and staff could attend conferences and other training efforts to learn best practices to enhance outcomes of the college’s guided pathways model. Findings from this study can be used to inform community college leaders about how to build academic program models to promote student success and completion rates. The findings from the study may also be used to help practitioners identify ways to increase on-time graduation rates.
Keywords: Guided pathways; Academic pathways; Student completion; Guided pathways model; Community colleges graduation rate; Academic issues